Performance Enhancement of Evaporated Thin Film Field Effect Transistors - Vallo, Frank J. (My University, 1969)
Evaporated thin film Field Effect transistors were investigated in an attempt to improve their performance. High resolution masks were constructed to facilitate the evaporation of the devices. Subsequent treatment was examined as a means of improving device stability. As well, some mask manipulation was tried as a means of reducing interelectrode capacitances.
The construction of the devices is discussed with particular reference to cleaning techniques. An attempt is made to relate instability problems in thin film devices to those encountered in MOS devices. Techniques such as mask construction, bonding, and packaging are also described.
Title: Performance Enhancement of Evaporated Thin Film Field Effect Transistors, Author: Frank J. Vallo, Location: Thode